Time to Align: A Call for Consensus on the Assessment of Genetic Testing - Erica Pitini; Valentina Baccolini; Giuseppe Migliara; Claudia Isonne; Alessandro Sindoni; Elena Mazzalai; Federica Turatto; Corrado De Vito; Carolina Marzuillo; Paolo Villari (Frontiers Media S.A., 2021)
In this paper, we updated our 2018 systematic review aimed to identify and compare ad hoc designed frameworks for genetic testing evaluation. Overall, we identified 30 frameworks (29 in the first systematic review and one in the update): they were mainly based on the ACCE model, whereas a minority were adjustments of the more traditional Health Technology Assessment (HTA) approach. After discussing the strengths and weaknesses of the retrieved frameworks, this perspective calls for consensus on the assessment of genetic testing. In line with the recent European recommendations that encouraged the generation of comparable evidence across Member States, we believe that the time has come to align all the ideas that have emerged over the last few decades and find a sustainable and sharable tool for the evaluation of genetic and genomic applications. Therefore, we suggest stopping the evaluation of such technologies using ad hoc strategies-affected by validation, implementation, and adoption issues-and we propose to use a general HTA approach, particularly the European reference tool for the assessment of health technologies, the EUnetHTA HTA core model, that is built on solid theoretical and methodological principles and provides a comprehensive assessment of the technologies value.